Effects of explosive type strength training on selected physical and technical performance characteristics in middle distance running - a case report - Mackala, K.; Józwiak, L.; Stodolka, J. (Polish Journal of Sport and Tourism, 2014)
Distance running performance is a simple function of developing high speeds and maintaining this speed as long as possible. Thus a correct running technique becomes an important component of performance. Technique is effective if the competitor can reach a better performance result with the same or lower energy consumption. The purpose of this investigation was to examine a six weeks application explosive type strength training on lower extremities power and maximum speed performance improvement in order to facilitate running technique in sub-elite male middle-distance runner. Material and methods. A sub-elite runner performed twice a week special exercises and running drills. He completed a pre and post-training jumping (SJ,CMJ,standing long jump, standing five jump) and speed (20 m from standing and flying start) field tests. For kinematical analysis, a video (SIMI Motion System) of a 10 m sprint from a 20 m flying start was collected. Results. Improvement occurred in all measurements but strong changes were evident in the 10 m from 20 flying start and in stride frequency from 3.90 to 4.01 Hz, due to decreasing of ground contact time from 160 to 156 ms. No strong evidence in the participant's running technique changes. Conclusion. This proved that six weeks of dynamic type strength program seems to improve neuromuscular characteristics of running speed and explosive power and no changes in running technique.